2018
DOI: 10.1002/adbi.201800138
|View full text |Cite
|
Sign up to set email alerts
|

Chip‐Based Heat Stimulation for Modulating Signal Propagation in HL‐1 Cell Networks

Abstract: Signal propagation in cardiac cell networks can be modulated by heat stimulation. Here, the response of a connected HL‐1 cardiomyocyte cell network to the application of confined heat stimuli using Ca2+ imaging is investigated. Localized temperature gradients are generated by resistive heating via microwire arrays on a chip surface, which serves as a substrate for growing a confluent cell network. It is demonstrated that upon heat stimulation, the velocity of the propagating Ca2+ wave in the network is locally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Cross-correlation analysis enabled us to construct isochronal maps that provided information about wavefront propagation velocities. We found that under normoxia, wavefronts propagated uniformly with an average speed of 18.9 ± 5.0 mm/s, which is typical for HL-1 cells . These characteristics were stable: another data set collected 10 min later showed a nearly identical propagation pattern and speed, 19.3 ± 5.0 mm/s (Figure d).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Cross-correlation analysis enabled us to construct isochronal maps that provided information about wavefront propagation velocities. We found that under normoxia, wavefronts propagated uniformly with an average speed of 18.9 ± 5.0 mm/s, which is typical for HL-1 cells . These characteristics were stable: another data set collected 10 min later showed a nearly identical propagation pattern and speed, 19.3 ± 5.0 mm/s (Figure d).…”
mentioning
confidence: 63%
“…We found that under normoxia, wavefronts propagated uniformly with an average speed of 18.9 ± 5.0 mm/s, which is typical for HL-1 cells. 41 These characteristics were stable: another data set collected 10 min later showed a nearly identical propagation pattern and speed, 19.3 ± 5.0 mm/s (Figure 2d). In contrast, 1% O 2 hypoxia for 1 h resulted in turbid propagation patterns that changed significantly between successive analyses performed 10 min apart (Figure 2e).…”
Section: T H Imentioning
confidence: 76%
“…Next, we considered the spatially extended versions of the models and focused on travelling wave solutions in 1D without external current. This is motivated by our interest in modelling propagation of activity in populations of cardiomyocytes similar to Czeschik et al (2015); Dang et al (2018); Yakushenko et al (2013). We start by analysing the 1D PDE in the singular limit ε = 0 in order to study the existence of travelling wave solutions.…”
Section: Discussionmentioning
confidence: 99%